Comparative Morphometrical Study of Proventriculus and Gizzard in Eurasian Collared Dove (Streptoplia decaocto) and Buzzard (Beuteo beuteo vulpinus) - Al-Musawi, Ridha Abbas; Al-Khakani, Salim Salih Ali (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background and Objective: The domestic dove, often known as the city dove or rock dove, is a subspecies of the rock dove. Domesticated birds began with the dove. The massive buzzard (Buteo buteo) inhabits many ecosystems across the globe. The Accipitridae family and Buteo genus include it. Buzzards hunt and eat alone, however, they may gather in flocks during the migration or when food is plentiful. Aims: Comparative Morphometrical Study in Proventriculus and Gizzard in Eurasian Collared Dove (Streptoplia decaocto) and Buzzard (Beuteobeuteo vulpinus). Materials and Methods: 7 adult healthy dove (streptopliadecaocto) and the same number of adult healthy common buzzard (beuteobeuteo vulpinus). were used in the present study, where obtained from a commercial market of AL-muthanaa city were used in the morphometrical study. Results: The proventriculus in the dove was a dark in colour with thin-wall fusiform-shaped, this tube was separated from the gizzard by an isthmus, the internal surface of the proventriculus appear shallow longitudinal folds. While in buzzard, it's a cone-shaped structure relatively with a thick and dark wall separated between the proventiculus and gizzard by an unclear isthmus, with a number of well-developed longitudinal folds called proventiculus folds. Gizzard in dove in this study revealed the gizzard usually located towards the abdomen, at the bottom of the thoracic cavity and at in abdominal inlet, between the liver lobes justly behind live left lobe and connected with the duodenum, appeared as disc or biconvex lens shape change in color from creamy to red-brown morphologically, and is lined with kaolin ( keratohyalin material) that appear yellowish to green in colour, while in buzzard located dorsocaudally to liver lobes towards the abdomen cavity, at dorsal part of the thoracic cavity, between the liver lobes, behind and connected with the duodenum and appear larger than liver lobes with shapes may range from pear to elongated, depending on the bird's unique anatomy and diet lining layer has very poor yellowish green pigment inside the gizzard. Conclusion: In general, and depending on the unique bird's anatomy and the diet programs, there are changes in the inner surface of the organs of Dove and Buzzard.